The Humanitarian Project-Based Material for Productive Written Language Skills Subject for English Education Study Program - Anggraini Thesisia Saragih; Amrin Saragih; Christine Helena; Yuni Khairina; Ade Namira (RIRAI Publisher, 2020)
This study was aimed to develop humanitarian project-based material for productive written language skills subject for English Education Study Program at UNIMED. Research and Development (R&D) was the design of this study with the subjects of the study were 25 students of first semester students of English Education Study Program at UNIMED. The research procedures were adapted from Borg and Gall’s research theory (1983) namely 1)gathering data and information, 2)need analysis, 3)designing course material, 4)validating and evaluating new course material by the Experts, 5)revising the course material and 6)final product. The instruments of collecting the data were questionnaire, interview and expert judgement questionnaire. The data were analyzed qualitatively and quantitatively.. Based on the result of the expert judgement, the whole aspects of developed materials were in the range of 81-100% and were categorized as “very good”.